Raman spectroscopy study of the interaction of 3,5,3 ′ -triiodo-L-thyronine with phosphatidylglycerol lipid bilayers - Sosa Morales, Marcelo Clemente (2015)
A Raman spectroscopic study of anionic model membranes and their structural alterations exerted by a relatively small biomolecule, such as the hormone 3,5,3′-triiodo-L-thyronine (T3), is presented. Spectral differences between pure dipalmitoylphosphatidylglycerol (DPPG) multilamellar vesicles and DPPG?T3 mixture and between pure dilauroylphosphatidylglycerol (DLPG) and DLPG?T3 mixture were evaluated in order to determine the response of lipid membranes in gel and liquid-crystalline phases to the hormone incorporation. Density functional theory (DFT) calculations support the band analysis of the complex 1150-1050 cm−1 Raman region. Geometry optimizations and vibrational behaviors of a model charged molecule that mimics the phosphatidylglycerol lipid moiety in solvated state were taken into account for the spectral interpretation of this specific region. The anionic nature of the lipid polar head plays an important role in the interaction with the hormone, as is evidenced by the C[DOUBLE BOND]O and PO2− stretching bands. In addition, the differential penetration of T3 into the hydrophobic region of the membranes shows to be dependent on the lipid phase. The spectral data were compared with those previously obtained for zwitterionic membranes.